Individualized Internal and External Training Load Relationships in Elite Wheelchair Rugby Players - Paulson, Thomas A. W.; Mason, Barry; Rhodes, James; Goosey-Tolfrey, Victoria L. (Frontiers in Physiology, 2015)
Aim: The quantification and longitudinal monitoring of athlete training load (TL) provides a scientific explanation for changes in performance and helps manage injury/illness risk. The aim of the present study was to establish the relationship between measures of internal (heart rate (HR) and session RPE (sRPE)) and external TL specific to wheelchair rugby (WR). Methods: Fourteen international WR athletes (age = 29 ± 7 yrs; body mass = 58.9 ± 10.9 kg) were monitored during 18 training sessions over a 3 month period. Activity profiles were collected during each training session using a radio-frequency based indoor tracking system. External TL was quantified by total distance (m) covered as well as time spent and distance covered in a range of classification-specific arbitrary speed zones. Banister’s TRIMP, Edwards’s summated HR zone (SHRZ) and Lucia’s TRIMP methods were used to quantify physiological internal TL. sRPE was calculated as the product of session duration multiplied by perceived exertion using the Borg CR10 scale. Relationships between external and internal TL were examined using correlation coefficients and the 90% confidence intervals (90% CI). Results: sRPE (r=0.59) and all HR-based (r >0.80) methods showed large and very large relationships with the total distance covered during training sessions, respectively. Large and very large correlations (r =0.56-0.82) were also observed between all measures of internal TL and times spent and distances covered in low and moderate intensity speed zones. HR-based methods showed very large relationships with time (r=0.71-0.75) and distance (r=0.70-0.73) in the very high speed zone and a large relationship with the number of high intensity activities performed (r=0.56-0.62). Weaker relationships (r=0.32–0.35) were observed between sRPE and all measures of high intensity activity. A large variation of individual correlation co-efficient was observed between sRPE and all external TL measures. Conclusion: The current findings suggest that sRPE and HR-based internal TL measures provide a valid tool for quantifying volume of external TL during WR training but may underestimate high intensity activities. It is recommended both internal and external TL measures are employed for the monitoring of overall TL during court-based training in elite WR athletes.